Design of a PID Speed Controller for BLDC Motor with Cascaded Boost Converter for High-Efficiency Industrial Applications - Al-Dabbagh, Zainab Ameer; Shneen, Salam Waley (International Journal of Robotics and Control Systems, 2025)
Achieving high voltage and efficiency in brushless direct current (BLDC) motor applications is challenging, particularly in industrial settings where precise speed control is essential. This study addresses this issue by designing a cascaded boost converter with a Proportional–integral–derivative (PID) speed controller. The cascaded boost converter is first simulated in an open-loop circuit using MATLAB/SIMULINK, followed by integrating the BLDC motor and adding a PID controller to achieve precise speed control. The PID controller achieved a steady-state speed of 1500 rad/s with an input voltage of 15 volts, resulting in an output voltage of over 50 volts. The efficiency of the system was improved by 87.87% compared to traditional methods. While the PID controller effectively controls the motor speed, it may consume more power and require more complex tuning in certain operating conditions. The proposed system is suitable for high-voltage industrial applications, such as electric vehicle drives and renewable energy systems, where precise speed control and high efficiency are critical.  The PID controller is user-friendly and easy to implement, making it suitable for various industrial applications. The system was tested under varying load conditions and input voltages to ensure robust performance and reliability. Future work will optimize the PID controller for real-time applications and integrate advanced control strategies to enhance system performance. A cascaded boost converter is a type of DC-DC converter that boosts the input voltage to a higher level, while a PID controller is a control loop feedback mechanism widely used for precise control of dynamic systems.